Anti-ulcerogenic activity of aqueous extract of ficus deltoidea against ethanol-induced gastric mucosal injury in rats - Zahra, M.A.S.F.; Salmah, I.; Suzita, M.N.; Hapipah, M.A.; Mahmood, A.A. (2009)
The ulcer healing activity of whole-plant extract of Ficus delroidea was studied in gastric ulcer induced by ethanol in rats. Four groups of adult male Sprague dawley rats were pre-treated respectively with distilled water (negative control), 250 and 500 mg kg -1 F. deltoidea extract (experimental) and omeprazole positive control) 30 min before oral. administration with absolute ethanol to generate gastric mucosal injury. After 1 h later, the rats were sacrificed and the ulcer areas and histological sections of gastric-walls were determined. Grossly, the negative control rats exhibited 7 mucosal injury whereas pre-treatment with F. deltoidea or omeprazole resulted in significantly less gastric mucosal lesions produced by ulcerogen's. The gastric protection was more prominent in 500 mg kg -1 F. deltoidea extra than 250 mg kg -1. Histological studies confirmed the results wherein compared to the pre-treated and thus cytoprotected groups of rats, the negative control rats showed very severe and deep gastric mucosal necrotic damage, along with edema and leucocytes infiltration of the submucosal layer. In conclusion, the present finding suggests that F. deltoidea extract promotes ulcer protection as ascertained by the comparative significant decreases in ulcer areas and inhibition of submucosal edema and leucocytes infiltration of submucosal layer. © Medwell Journals, 2009.